2021
DOI: 10.1101/2021.04.20.440678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sentinel cells enable genetic detection of SARS-CoV-2 Spike protein

Abstract: The COVID-19 pandemic has demonstrated the need for exploring different diagnostic and therapeutic modalities to tackle future viral threats. In this vein, we propose the idea of sentinel cells, cellular biosensors capable of detecting viral antigens and responding to them with customizable responses. Using SARS-CoV-2 as a test case, we developed a live cell sensor (SARSNotch) using a de novo-designed protein binder against the SARS-CoV-2 Spike protein. SARSNotch is capable of driving custom genetically-encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…We previously demonstrated that the de-novo designed LCB1 and LCB3 minibinders for SARS-CoV-2 Spike protein could be used as functional antigen sensors when integrated with synNotch 18 . These anti-SARS Notch constructs successfully detected both purified Spike protein and Spike expressed on the surface of mammalian cells in a model of virally-infected cells to drive a synthetic transcriptional output.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that the de-novo designed LCB1 and LCB3 minibinders for SARS-CoV-2 Spike protein could be used as functional antigen sensors when integrated with synNotch 18 . These anti-SARS Notch constructs successfully detected both purified Spike protein and Spike expressed on the surface of mammalian cells in a model of virally-infected cells to drive a synthetic transcriptional output.…”
Section: Resultsmentioning
confidence: 99%
“…See Supplemental Figure 1A for schema of output circuit and SNIPR expression constructs. We incubated a polyclonal population of SNIPRexpressing cells with either untransduced K562 cells or K562s stably expressing a prefusion stabilized version of the SARS-CoV-2 Spike ectodomain 41 displayed on a PDGFR transmembrane domain as previously described 18 (Figure 1B). After 72 hours, we assessed our output circuit-only expressing Jurkat cells (No Notch) and LCB1and LCB3-SNIPR expressing cells for BFP expression (Figure 1C).…”
Section: Minibinders Adapt Readily To Next-generation Synthetic Prote...mentioning
confidence: 99%
“…WT-fl-Spike protein was purified based on the previously described protocol (Weinberg et al, 2021) 30ml of ExpiCHO-S cells at 6M cells/mL were transfected with 1ug/mL of the spike WT using the ExpiCHO TM Expression System Kit (Gibco, catalog # A29133) following the manufacturer’s Standard protocol. Briefly, the transfected cells were shaken at 37°C and 8% CO 2 and 18 hours post-transfection, the cultures were supplemented with ExpiCHO TM Feed and ExpiFectamine TM CHO Enhancer and continued to be shaken at 37°C and 8% CO 2 for up to 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were co-cultured for 72 hours and the BFP expression and surface expression of receptors and ALFA-tag were conducted using flow cytometry. synNotch and SNIPR activation was assessed as described previously by fitting a two-component Gaussian mixture model to BFP expression data and estimating the fraction of the population in the 'off' and 'on' components 41 . SNIPR Activation-Ngn2 Differentiation Assay mESCs expressing SNIPR constructs were seeded at a density of 1e4 cells/well in a lowattachment round bottom 96-well plate.…”
Section: Antibodiesmentioning
confidence: 99%